Generalized Findlay-Grubert Theorem - Borkakoti, Jitendralal (Quarterly Journal of Economics, 1980)
This generalization allows the relative price to vary and explicitly considers Hicks-, Harrod-, and Solow-neutrality. Under certain conditions, the Harrod-neutral and the Solow-neutral shifts are equivalent to the Hicks factor-saving shift. If Hicks-Harrod-Solow neutral or the Hicks factor-saving improvement occurs in one of the two sectors, then the relative price of that good falls, and the level of output of that good increases. However, the level of output of the other good remains constant if Hicks-Harrod-Solow-neutral progress occurs, and decreases or increases according to whether the Hicks x-saving or x-using technological progress occurs in the x-intensive sector.